Metagenomic Next-Generation Sequencing for Pathogen Detection and Transcriptomic Analysis in Pediatric Central Nervous System Infections. (6th March 2021) - Ramchandar, Nanda; Coufal, Nicole G; Warden, Anna S; Briggs, Benjamin; Schwarz, Toni; Stinnett, Rita; Xie, Heng; Schlaberg, Robert; Foley, Jennifer; Clarke, Christina; Waldeman, Bryce; Enriquez, Claudia; et al.
Abstract: Background: Pediatric central nervous system (CNS) infections are potentially life-threatening and may incur significant morbidity. Identifying a pathogen is important, both in terms of guiding therapeutic management and in characterizing prognosis. Usual care testing by culture and polymerase chain reaction is often unable to identify a pathogen. We examined the systematic application of metagenomic next-generation sequencing (mNGS) for detecting organisms and transcriptomic analysis of cerebrospinal fluid (CSF) in children with central nervous system (CNS) infections. Methods: We conducted a prospective multisite study that aimed to enroll all children with a CSF pleocytosis and suspected CNS infection admitted to 1 of 3 tertiary pediatric hospitals during the study timeframe. After usual care testing had been performed, the remaining CSF was sent for mNGS and transcriptomic analysis. Results: We screened 221 and enrolled 70 subjects over a 12-month recruitment period. A putative organism was isolated from CSF in 25 (35.7%) subjects by any diagnostic modality. Metagenomic next-generation sequencing of the CSF samples identified a pathogen in 20 (28.6%) subjects, which were also all identified by usual care testing. The median time to result was 38 hours. Conclusions: Metagenomic sequencing of CSF has the potential to rapidly identify pathogens in children with CNS infections. Abstract : We examined the utility of next-generation sequencing in comparison to usual care in detecting a pathogenic organism in children with central nervous system infections.